The Development Of Discovery Learning-Based Geometry Transformation Teaching Materials To Improve Student's Understanding And Increase Students' Interest In Class Ix Junior High School - Aprilianti Marpaung (Indonesian Journal of Education and Mathematical Science, 2022)
This study aims to determine the procedure for developing Geometry Transformation Teaching Materials based on Discovery Learning to improve the understanding and learning interests of Class IX Junior High School Students. The model used in this study was a 4D development model that has been modified into 3D, which consisted of Definition, Design, and Development. Based on the validation results from lecturers and media experts, it was obtained 4.47 and 4.34. From these results, it was stated that discovery learning-based geometry transformation teaching materials were appropriate to be used as learning media.